IMPROVING CHILDREN'S MORALS AND INTEREST IN LEARNING THROUGH TUTORING AND OUT BOUND MEDIA - Nur Khaulawi; Sulkifli; Afit Rizal Susanto; Titis Rosowulan (khidmatan, 2023)
The quality of human resources is essentially determined by education. Through tutoring and outbound activities, it is proven that children's education is not only obtained at school, this activity is intended to be able to provide learning for children to be able to have good character traits. The activity method uses a theoretical approach and a practical approach. With the PAR (Participatory Action Research) approach, the service team views that the existence of tutoring and outbound activities for children is an important asset. The results of this development for children in outbound have a direct impact on the formation of morals, character and recreation in students, so as to improve the quality of education and skills. student. Tutoring and outbound is one of the learning methods that is a new breakthrough so that children can learn comfortably and feel happy. This is considered important as an effort so that children grow up to be active individuals.